MEDIUM OPTIMIZATION FOR THE PRODUCTION OF BIOMASS BY Cunninghamella sp. 2A1 USING RESPONSE SURFACE METHODOLOGY - Siti Aminah Sulaiman; Aidil Abdul Hamid; Wan Mohtar Wan Yusoff (Universitas Gadjah Mada, 2005)
A statistical design approach has been used to optimize the production of biomass byCunninghamellasp. 2A1, evaluated based on lipidless biomass. A 23full factorial centralcomposite design (CCD) was chosen to study the combined effects of three factors; ammoniumtartrate, peptone and glucose concentrations. The p-value for each factors was < 0.05 suggestingthat these factors have significant effect on the production of lipidless biomass. The productionis represented by a linear model with p-value < 0.0001. The optimized medium consists of 3.86g/l ammonium tartrate, 55.84 g/l glucose and 7.73 g/l peptone predicted 16.83 g/l lipidlessbiomass. Results from four replications based on the optimized medium produced 18.48 g/llipidless biomass, which are in close agreementwith the predicted value. The coefficient forglucose was the highest indicating it as the most significant factoraffecting lipidless biomassproduction.